TEACHERS’ STRATEGIES IN TEACHING SPEAKING TO TENTH GRADE STUDENTS AT SMK NEGERI 3 MEDAN - Anggita Bella; Puan Suri Mira Annisa Sembiring (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2023)
This research is about teachers strategies in teaching speaking to tenth grade students at SMKN 3 Medan. The aims of this study are (1) to analyze the strategies used by English teachers in teaching speaking to tenth grade students, and (2) to find out the difficulties by teachers in implementing the strategy to tenth grade students. The subject of this study were two English teachers at SMKN 3 Medan. This study used descriptive qualitative research. Research data collection was done by observation, video recording and interviews. The result of this study are, (1) The first teacher applied the strategies in teaching speaking, namely question for understanding, showing and telling, students working together, plenty of practice and flexible time. The second teacher applies showing and telling, plenty of practice, flexible time and students working together. The two English teachers did not apply clear lesson goals, summarizing, providing students with feedback, teach strategies not just content, and nurture metacognition.  It is known that the two English teachers of ten grade students in SMKN 3 Medan have not implemented the ten strategies in teaching speaking process. (2) it was found that both teachers had difficulties in implementing the strategies in teaching speaking. The difficulties faced by the two of teachers are the same, namely inhibition, nothing to say, low in participation and mother   tongue use.